Assessing crop evapotranspiration and edaphoclimatic variability for basil (Ocimum basilicum L.) under ENSO-modulated tropical conditions in Colombia - Beltran-Medina, Jose Isidro; Ouazaa, Sofiane; Chaali, Nesrine; Jaramillo Barrios, Camilo Ignacio; Pedroza Berrío, Kelly Johana; Hoyos Cartagena, Jose Alvaro; Calderón Carvajal, John Edinson (Frontiers in Soil Science, 2025)
Basil (Ocimum basilicum L.) is a high-value aromatic crop with growing global demand, and optimizing its yield under tropical conditions is critical for sustainable agriculture. This study aimed to (1) quantify basil crop coefficient (Kc) and evapotranspiration (ETc) via lysimeters and (2) characterize soil physical–chemical variability across three Tolima (Colombia) region sites: Mariquita, Honda, and El Espinal. Crop evapotranspiration, measured via lysimeters, peaked at 7.41 mm day-1 during maturity, with a total crop water requirement of 228.82 mm. Crop coefficients varied dynamically by stage, with values of 0.75, 0.98, and 0.76 during establishment, peak growth, and senescence, respectively. Historical climate analysis revealed a bimodal rainfall distribution modulated by ENSO phenomenon, with El Niño-La Niña phases, with significant impacts on crop water availability. Soil analyses showed that Mariquita soils are higher in total porosity Tp (47.80%), organic matter (2.42 g 100g-1), field capacity FC (31.62%), and available water (3.59%), whereas El Espinal showed higher bulk density (1.65 gr cm-3) and permanent wilting point PWP (21.99%), constraining water availability. Honda soils presented intermediate conditions but were notable for higher cation exchange capacity CEC (9.55 cmol kg-1) and moderate organic matter content (1.56 g 100g-1), supporting balanced nutrient retention. Cultivated plots across sites showed increased phosphorus and copper relative to adjacent natural areas, reflecting fertilization practices. These results highlight the need for precision irrigation scheduling and site-specific soil management to maximize water productivity and yield stability. Our findings provide a baseline for adapting basil production systems to climatic variability in tropical dry regions.